2022
DOI: 10.1186/s12889-022-13873-8
|View full text |Cite
|
Sign up to set email alerts
|

Educational intervention program based on health belief model and neck pain prevention behaviors in school teachers in Tehran

Abstract: Background Prevention of musculoskeletal disorders as one of the most common occupational health problems among the working population in both developed and developing countries is an important necessity and priority. The aim of this study was to evaluate the effectiveness of an educational intervention program based on the Health Belief Model (HBM) to increase awareness, perceived sensitivity, perceived severity, perceived benefits, and self-efficacy in adopting neck health-promoting behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Considering that elderly suffer from various diseases such as musculoskeletal pain, the main purpose of this study was to design a multimodal intervention based on HBM to obtain preventive behaviors of musculoskeletal pain in the elderly. The positive effect of interventions on teachers [ 47 ] as well as combined programs (supplement consumption and physical activity) based on HBM [ 48 ] has been proven. Various studies have also confirmed the positive effect of HBM-based interventions [ 49 , 50 ] and the effect of multimodal interventions on reducing pain in the elderly [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that elderly suffer from various diseases such as musculoskeletal pain, the main purpose of this study was to design a multimodal intervention based on HBM to obtain preventive behaviors of musculoskeletal pain in the elderly. The positive effect of interventions on teachers [ 47 ] as well as combined programs (supplement consumption and physical activity) based on HBM [ 48 ] has been proven. Various studies have also confirmed the positive effect of HBM-based interventions [ 49 , 50 ] and the effect of multimodal interventions on reducing pain in the elderly [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…27 However, an intervention grounded in the health beliefs model resulted in improvements in health-promoting practices related to neck well-being among school children in Tehran. 28 In addition, a systematic review found there was a lower risk of nonspecific neck pain in those who frequently engage in physical activity. 29 Furthermore, in 2021, a large-scale survey showed that Tehran had one of the lowest levels of physical activity in Iran, while Kohgiluyeh and Boyer-Ahmad was among the highest.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a cross‐sectional study of 586 school teachers in Tehran showed the annual prevalence of neck pain was 37% 27 . However, an intervention grounded in the health beliefs model resulted in improvements in health‐promoting practices related to neck well‐being among school children in Tehran 28 . In addition, a systematic review found there was a lower risk of nonspecific neck pain in those who frequently engage in physical activity 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have suggested that timely and accurate intervention is the main means of preventing the occurrence and development of neck pain. [44][45][46] Therefore, targeted interventions for inducing factors of neck pain will be of great value to the neck health of students during online learning. Next, this study examines the long-term effects of participants' behavior during online learning and develops scientific intervention programs to address risk factors, improve student health, and prevent the occurrence and deterioration of neck pain.…”
Section: Future Considerationmentioning
confidence: 99%